2013
DOI: 10.3390/ijms140510570
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Species Bacterial Quorum Sensing Studied at Single Cell Level in a Double Droplet Trapping System

Abstract: In this paper, we investigated the intra-species bacterial quorum sensing at the single cell level using a double droplet trapping system. Escherichia coli transformed to express the quorum sensing receptor protein, LasR, were encapsulated in microdroplets that were positioned adjacent to microdroplets containing the autoinducer, N-(3-oxododecanoyl)- l-homoserine lactone (OdDHL). Functional activation of the LasR protein by diffusion of the OdDHL across the droplet interface was measured by monitoring the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Extending these findings to predict the activity within more complex multispecies microbial ecosystems will require a combination of predictive theoretical models and perhaps new experimental tools to quantify interactions. With the rapid development of nanofabrication technology, microfluidic devices are widely used for single-cell analysis [ 41 , 42 ], allowing us to study multispecies interactions at the microsystem level such as suggested in Fig 4 and elsewhere [ 43 , 44 ]. We implemented a model in Fig 4 to explore how the species evenness and the interaction network set the overall ecosystem outputs.…”
Section: Discussionmentioning
confidence: 99%
“…Extending these findings to predict the activity within more complex multispecies microbial ecosystems will require a combination of predictive theoretical models and perhaps new experimental tools to quantify interactions. With the rapid development of nanofabrication technology, microfluidic devices are widely used for single-cell analysis [ 41 , 42 ], allowing us to study multispecies interactions at the microsystem level such as suggested in Fig 4 and elsewhere [ 43 , 44 ]. We implemented a model in Fig 4 to explore how the species evenness and the interaction network set the overall ecosystem outputs.…”
Section: Discussionmentioning
confidence: 99%
“…However, upon their adjustment to prolonged mammalian assays, they require multilayer fabrication, either involving high-pressure cell loading or not allowing for different substrates to be used (26,27). Several single-cell platforms that encapsulate cells in stationary droplet arrays are available (5,(28)(29)(30)(31)(32)(33)(34)(35); however, the ability to culture adherent cells for long periods remains difficult (36).…”
mentioning
confidence: 99%
“…2013). In E. coli, quorum sensing was investigated at the single-cell scale using a double droplet-based microfluidic system enabling to encapsulate two individual cells separately into two adjacent droplets which can communicate by means of diffusion of signal molecules across the droplets (Bai et al, 2013). Using strains carrying a GFP construction under the control of the quorum sensing receptor protein LasR, the activation of quorum sensing was analyzed via the monitoring of GFP expression in an individual cell in a droplet in response to autoinducers produced by the cell in the adjacent droplet.…”
Section: Resident Biofilms As Hot Spots For Pathogen Persistencementioning
confidence: 99%